PENGENALAN APLIKASI BUKU KAS KEPADA PELAKU UMKM SEKITARAN MEDAN PANCING - Siti Aisyah; Ghilman Rozy Hrp; Rio Ariangga Hutagalung; Helva Diansyah Putri; Indah Wulansari; Utami RA Padang (Universitas Muhammadiyah Manado, 2022)
Recording income and expenses in running a business is something that must be applied when carrying out a business activity. Notes or books are very important in human life in rewriting to be used as a reminder and to record important things. Financial Recording is very important as a business actor but many MSME actors forget this. The importance of digital financial literacy can help record financial transactions and make it easier to recap product sales data, then an innovation emerges. An application on the smartphone Buku Khas. Therefore, the purpose of this Community Service is to educate and teach MSME actors to use the Special Book Application. The results of the study show that there are still many MSME actors who still record finances by writing them in a book, therefore the researcher is conducting community service with the theme of introducing technology to MSMEs in order to facilitate business continuity.